The Relationship of Some Liver Function Tests and Red Blood Cell Parameters With Disease Outcome of Patients With COVID-19 Admitted to Razi Hospital, Rasht, Northern Iran - lida mahfoozi; mohammad haghighi; Sepinood Rezaei; paridokht karimian (مجله دانشگاه علوم پزشکی گیلان)
Background The presence of anemia and liver function disorders are associated with higher mortality rates in patients with COVID-19, but studies on the relationship of red blood cell parameters and liver function tests with the outcome of these patients are limited. Objective This study aimed to investigate the relationship between some liver function tests and red blood cell parameters with the disease outcome of hospitalized patients with COVID-19 in northern Iran. Methods This cross-sectional study was conducted on 195 patients with COVID-19 admitted to Razi Hospital in Rasht (as a corona treatment center) in 2021. Demographic information and laboratory tests including aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALKP), prothrombin time (PT), total bilirubin, hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), disease outcome (recovery or death) and duration of hospitalization were recorded. Data analysis was done in SPSS software, version 26. Results The mean age of patients was 58.92±16.39 years. Among patients, 54.4% were female. Mean age (P<0.001), total bilirubin (P=0.024), and PT (P=0.004) were significantly associated with disease outcomes. Also, there was a significant relationship between mean Hb (P=0.004) and HCT (P=0.002) with patients’ hospitalization length. Conclusion Age, total bilirubin and PT are related to disease outcomes in patients with COVID-19. Also, the decrease in Hb and HCT is associated with increased hospitalization length in these patients.